Precision and accuracy of commercial assays for vancomycin therapeutic drug monitoring: evaluation based on external quality assessment scheme. (28th May 2020) - Chen, Chao-Yang; Li, Meng-Ya; Ma, Ling-Yun; Zhai, Xing-Yu; Luo, Dao-Huang; Zhou, Ying; Liu, Zhen-Ming; Cui, Yi-Min
Abstract: Background: Vancomycin remains a mainstay of the treatment of Gram-positive bacterial infections. It is crucial to accurately determine vancomycin serum concentration for adequate dose adjustment. Objectives: To evaluate the precision and accuracy of commercial assay techniques for vancomycin concentration and to assess the comparability of vancomycin detection methods in Chinese laboratories. Methods: Human serum samples spiked with known concentrations of vancomycin were provided to laboratories participating in the external quality assessment scheme (EQAS). Assay methods included chemiluminescence, enzyme immunoassay (EIA) and so on. The dispersion of the measurements was analysed and the robust coefficient of variation (rCV), relative percentage difference (RPD) and satisfactory rate for method groups were calculated. Moreover, performance of the Chinese laboratories was assessed. Results: A total of 657 results from 75 laboratories were collected, including 84 samples from 10 Chinese laboratories. The median rCV, median RPD and satisfactory rates classified by methods ranged from 1.85% to 15.87%, −14.75% to 13.34% and 94.59% to 100.00%, respectively. Significant differences were seen in precision, between kinetic interaction of microparticles in solution (KIMS) and other methods, and in accuracy, between enzyme-multiplied immunoassay technique (EMIT), fluorescence polarization immunoassay (FPIA) and other techniques. Vancomycin detection in China mainly depended on the chemiluminescence and EMIT methods, which tended to result in lower measurements. Conclusions: Although almost all assays in this study achieved an acceptable performance for vancomycin serum concentration monitoring, obvious inconsistencies between methods were still observed. Chinese laboratories were more likely to underestimate vancomycin concentrations. Thus, recognizing inconsistencies between methods and regular participation in vancomycin EQAS are essential.